Comparing Mummification Processes: Egyptian and Inca - Emma J. J. Williams (EXARC Journal)
This two-year research project was carried out as part of SUNY Potsdam’s Presidential Scholars program which allows undergraduates to conduct independent research. The project employs controlled laboratory experiments to compare desiccation rates in natural and artificial mummification processes while considering the cultural context of the funerary practices. Artificial mummification techniques of the Egyptian and Inca cultures are considered. Natural mummification includes artificial heating and cooling of the carcass buried in sand within a clay pot. Egyptian mummification requires evisceration of the carcass, treatment with alcohol to limit bacterial activity, and submergence in Natron. Inca mummification necessitates evisceration and skinning of the carcass, use of alcohol, and drying of the specimen. Rat carcasses were used in place of human cadavers, with full documentation of the process, duration, and stages of their mummification. The lab protocols established by this research will provide protocols for future taphonomic studies. This research emphasizes the necessity for considering the cultural context of taphonomy. Understanding the taphonomy of desiccated tissues is directly relevant in bioarchaeological applications.